All-solid continuous-wave Nd: YVO4-diamond intracavity Raman laser - Yunpeng Cai; Yaxuan Duan; Hui Chen; Bingzheng Yan; Yaoyao Qi; Zhenxu Bai; Yulei Wang; Zhiwei Lu; Jie Ding (Functional Diamond)
We demonstrated a continuous intracavity diamond Raman laser operating by linear-cavity and V-cavity design. The diamond crystal as the Raman medium and Nd: YVO4 as the laser gain medium was utilized to achieve high beam quality Stokes output with narrow line width. By employing linear and V-shaped cavity, we achieved Stokes light outputs of 1.68 and 2.26 W, respectively. Compared to the linear cavity, the V-shaped cavity has a higher conversion efficiency of 11.07% and a narrower linewidth of 0.07 nm. Mechanism for linewidth of different cavity design and methods for further increasing power range and high quality are discussed.